Feed Analysis of a Hexagonal Microstrip Patch Antenna - N., Sivasankari; A., Kaleeswari; A., Padmatharshini (IRO Journal on Sustainable Wireless Systems, 2025)
The feeding methods of coaxial, microstrip line, and proximity-coupled feeds significantly influence the performance of microstrip patch antennas. While proximity-coupled microstrip patch antennas have been explored for various applications, there remains a lack of understanding regarding the optimal positioning and length of the proximity-coupled feed. This study investigates the impact of feed line length on the performance of a proximity-coupled microstrip patch antenna. The findings reveal that the resonance frequency is directly affected by the length of the feed line; specifically, as the feed line length increases, the antenna resonates at a higher frequency.